From input subsidies to compensating farmers for soil health services - Campbell, Bruce M.; Nyirongo, Jacob; Botha, Blessings; Duchoslav, Jan; Munthali, Moses W.; Nyondo, Christone; Sunga, Ishmael; Wollenberg, Eva Karoline (2023)
- In many countries in Southern and Eastern Africa, input subsidy programmes are common, often focussing on inorganic fertiliser. These programmes often do not achieve their food security objectives, partly because soil health is in decline as a result of years of application of inorganic fertilisers in the absence of other soil ameliorative measures. - Solutions to soil health decline are well known, and include various combinations of fallowing, crop diversification, intercropping and crop rotations (especially legume rotations), soil organic matter additions, liming and applications of the appropriate inorganic fertilisers. But many of these come with significant socio-economic and technical challenges to farmers. - A way forward is through compensating farmers for soil health services, which will generate a multitude of private and public benefits. This would be a form of Payment for Environmental Services (PES), as supported in the global initiative CompensACTION,1 led by the German Federal Ministry of Economic Cooperation and Development (BMZ). - Nine recommendations for implementing a soil health payment scheme are presented, some of which focus on the broader enabling environment. - Development partners can support the implementation of Payments for Soil Heath Services schemes by: assisting countries in establishing pilot schemes for lessons learning; supporting longer term monitoring of soil health changes; supporting government efforts to repurpose subsidy policies; and facilitating public-private partnerships to leverage in private sector investment in activities that will enhance soil health.